2021
DOI: 10.1007/s10661-021-09580-3
|View full text |Cite
|
Sign up to set email alerts
|

Cold traps as reliable devices for quantitative determination of SARS-CoV-2 load in aerosols

Abstract: Spread of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is a demanding challenge. This is of particular importance in schools and public areas of unavoidable access. New viral mutations may increase infectivity and require even better methods to identify areas of potential hazards. High-throughput SARS-CoV-2 testing and legal restrictions are not effective in order to get the current outbreak under control. The occurrence of new SARS-CoV-2 variants with a higher transmissibility require… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Research on animals has shown that inhalation of an atomised solution leads to greater infection and mortality rates than dry intranasal inoculation when exposed to the same amount of virus [103]. Research has examined the physics of deposition in the respiratory tract concerning medication transport and dosimetry of nebuliser treatments, as mentioned in reviews [104].…”
Section: Latest Case Studiesmentioning
confidence: 99%
“…Research on animals has shown that inhalation of an atomised solution leads to greater infection and mortality rates than dry intranasal inoculation when exposed to the same amount of virus [103]. Research has examined the physics of deposition in the respiratory tract concerning medication transport and dosimetry of nebuliser treatments, as mentioned in reviews [104].…”
Section: Latest Case Studiesmentioning
confidence: 99%